Percutaneous nephrolithotomy, ileal conduit- lithotripsy and litholapaxy for a neglected encrusted ureteral stent (2017)
Urolithiasis can result as a complication of urinary diversión, favored by urinary stasis, intestinal mucus, urinary tract bacteriuria, the metabolic derangements and the presence of foreign bodies. We present a 52- year-old male who underwent radical cystectomy with construction of a Bricker uretero-ileostomy. 5 years later he was found with a forgotten ureteral stent, a 6 cm calculi occupying the whole ileal conduit and a 13 mm calculi in the left renal pelvis. We present our experience in the successful endourological management of an encrusted neglected ureteral stent in an ileal conduit, achieving a stone-free status without complications. © 2017 The Authors